The Correlation Between HOTS, Reading Interest and Reading Comprehension - Sri, Handayani; Fhara, Charista; Imroatul, Ma'fiyah (Peneliti.net, 2024)
The goals of this research are: 1) to find out if there is a strong connection between Higher Order Thinking Skills (HOTS) and Reading Comprehension. 2) to find out if there is a strong connection between Reading Interest and Reading Comprehension. 3) to find out if there is a strong correlation between students' HOTS, Reading Interest and Reading Comprehension. This study took place at the eleventh grade of SMAN 1 Colomadu during the 2022/2023 Academic Year. The researcher used a type of research that looked at numbers and relationships between things whic is correlation research. This study involved 26 students who were chosen to be part of the research. The students were selected randomly for the study. The researcher used different ways to collect data, including tests and not tests. For the test, there are 20 questions that measure how well students HOTS and reading comprehension. For the non-test method, the researcher used a set of questionnaire to find out how interested students are in reading. The researcher used multiple linear regression to examine the data. The results of this study showed that : 1) there is a strong connection between a student's HOTS and their reading comprehension. The data analysis shows that the t-value 4. 102 is higher than the t-table value 2. 0342. 2) there is no significant correlation between students’ reading comprehension and reading interest. The data analysis shows that the value of t (0. 008) is less than the ttable value (2. 034). 3) there is weak correlation between HOTS, reading interest and reading comprehension. Based on the analysis of the data, the value of F (8,595) is greater than the value of Ftable (3,28). The findings of this study are expected to inspire students to read more and enhance their abilities to understand what they read and think critically. This research wants teachers to be more imaginative and inventive when they teach reading material. This research can help other researchers who are studying HOTS, reading interest, and reading comprehension.